Blood at the Root - Williams, LaDarrion (Labyrinth Road, 2024)
"Ten years ago, Malik's life changed forever the night his mother mysteriously vanished and he discovered he had uncontrollable powers. Since then, he has kept his abilities hidden, looking out for himself and his younger foster brother, Taye. Now, at 17, Malik is finally ready to start a new life for both of them, far from the trauma of his past. However, a daring act to rescue Taye reveals an unexpected connection with his long-lost grandmother: a legendary conjurer with ties to a hidden magical university that Malik's mother attended"--Provided by publisher.